Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1039/c9cp02558h
|View full text |Cite
|
Sign up to set email alerts
|

Does induced current density explain the C–H and C–F Perlin effects?

Abstract: One-bond spin–spin coupling constant (SSCC) data may be useful in providing information on the stereochemistry and intramolecular interactions in molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Similarly, in the normal Perlin effect correlations of the Δ R (C–F) ax‑eq indicator increase (positive values) the Δ­( 1 J C–F ) ax‑eq indicator in the opposite direction. These correlations manifest the stereoelectronic origin of the normal and reverse Perlin effects composed of three energy componentssteric, hyperconjugative, and electrostaticadvanced by Freitas and co-workers. ,, …”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…Similarly, in the normal Perlin effect correlations of the Δ R (C–F) ax‑eq indicator increase (positive values) the Δ­( 1 J C–F ) ax‑eq indicator in the opposite direction. These correlations manifest the stereoelectronic origin of the normal and reverse Perlin effects composed of three energy componentssteric, hyperconjugative, and electrostaticadvanced by Freitas and co-workers. ,, …”
Section: Resultsmentioning
confidence: 63%
“…In contrast for hypohalides and amino substituents, the normal Perlin effect (|( 1 J C–F ) eq | > |( 1 J C–F ) ax |) observed by Perlin and Casu is observed. The normal and reverse Perlin effects have been extensively studied in fluorinated six-membered rings, ,,,, but their origin remains debatable. Freitas’s group ,, thoroughly investigated the factors tuning the fluorine Perlin-like effects in 2-fuoro­tetrahydropyran and 2-, 3-, and 4-fluoro-substituted piperidine derivatives and provided a general interpretation based predominantly on dipolar and not hyperconjugative interactions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As far as we know studies on the conformational behavior of fluorinated tetrahydropyran rings to understand the stereoelectronic influences of fluorine on molecular conformations are limited, [10][11][12][13][14][15][16][17][18][19] relative to the rich literature concerning the studies on fluorine effects in tuning the electronic profiles in medicinal and bioorganic chemistry. 20,21 Xu et al 10 showed that it is possible to restore the exo-anomeric effect of an acetal or natural sugar when replacing one of the oxygen atoms at the endocyclic position by a CF 2 group.…”
Section: Introductionmentioning
confidence: 99%